PPARγ and PPARα synergize to induce robust browning of white fat in vivo - Tobias Kroon; Matthew Harms; Stefanie Maurer; Laurianne Bonnet; Ida Alexandersson; Anna Lindblom; Andrea Ahnmark; Daniel Nilsson; Peter Gennemark; Gavin O'Mahony; Victoria Osinski; Coleen McNamara; et al. (Elsevier, 2020)
Objective: Peroxisome proliferator-activated receptors (PPARs) are key transcription factors that regulate adipose development and function, and the conversion of white into brown-like adipocytes. Here we investigated whether PPARα and PPARγ activation synergize to induce the browning of white fat. Methods: A selection of PPAR activators was tested for their ability to induce the browning of both mouse and human white adipocytes in vitro, and in vivo in lean and obese mice. Results: All dual PPARα/γ activators tested robustly increased uncoupling protein 1 (Ucp1) expression in both mouse and human adipocytes in vitro, with tesaglitazar leading to the largest Ucp1 induction. Importantly, dual PPARα/γ activator tesaglitazar strongly induced browning of white fat in vivo in both lean and obese male mice at thermoneutrality, greatly exceeding the increase in Ucp1 observed with the selective PPARγ activator rosiglitazone. While selective PPARγ activation was sufficient for the conversion of white into brown-like adipocytes in vitro, dual PPARα/γ activation was superior to selective PPARγ activation at inducing white fat browning in vivo. Mechanistically, the superiority of dual PPARα/γ activators is mediated at least in part via a PPARα-driven increase in fibroblast growth factor 21 (FGF21). Combined treatment with rosiglitazone and FGF21 resulted in a synergistic increase in Ucp1 mRNA levels both in vitro and in vivo. Tesaglitazar-induced browning was associated with increased energy expenditure, enhanced insulin sensitivity, reduced liver steatosis, and an overall improved metabolic profile compared to rosiglitazone and vehicle control groups. Conclusions: PPARγ and PPARα synergize to induce robust browning of white fat in vivo, via PPARγ activation in adipose, and PPARα-mediated increase in FGF21.